2006
DOI: 10.1348/014466505x29099
|View full text |Cite
|
Sign up to set email alerts
|

Paranoia and emotion perception across the continuum

Abstract: Instead of an enhanced sensitivity for the recognition of emotional states, higher levels of paranoia were linked to a performance deficit on emotion perception tasks. The deficits in emotion perception may reflect the increased skepticism and scrutiny associated with posed emotion tasks (Davis & Gibson, 2000). Research should begin to focus on the underlying mechanisms of emotion perception deficits in paranoia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 57 publications
5
39
0
Order By: Relevance
“…Differences in terms of reactions to paranoid beliefs were expected, even though paranoia is a shared thought process across all individuals. Results showed that paranoia was present across the four groups, as measured by the PEPS and in consonance current findings on the continuity of paranoid ideation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)30). That is, all individuals presented, to some extent, convictions about others' intentions to harm them.…”
Section: Running Head: Reactions To Paranoia In Clinical and Non-clinsupporting
confidence: 87%
See 3 more Smart Citations
“…Differences in terms of reactions to paranoid beliefs were expected, even though paranoia is a shared thought process across all individuals. Results showed that paranoia was present across the four groups, as measured by the PEPS and in consonance current findings on the continuity of paranoid ideation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)30). That is, all individuals presented, to some extent, convictions about others' intentions to harm them.…”
Section: Running Head: Reactions To Paranoia In Clinical and Non-clinsupporting
confidence: 87%
“…Paranoid ideation has been regarded a continuous cognitive construct (1)(2)(3)(4)(5)(6), as several studies have been supporting over the past decades (7)(8)(9)(10)(11). However, the link between clinical and sub-clinical paranoia and the etiology of paranoid beliefs is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palavras chave: processos cognitivos, processos de grupo e interpessoais, perceção e cognição social A significant body of evidence on the continuity of paranoid experience has supported current conceptualizations of this phenomena as a cognitive and social process that is manifested over a continuum (Célia Barreto Carvalho, Pinto-Gouveia, Peixoto, & Motta, 2014;Combs, Michael, & Penn, 2006;Freeman, Pugh, Vorontsova, Antley, & Slater, 2010;Nuevo et al, 2012). Thus, paranoid ideation can present itself as a normative phenomenon, such as mistrust feelings that occasionally arise in individuals without psychiatric problems, or present itself in more dysfunctional and inflexible fashion, constituting specific psychopathological symptoms (e.g.…”
mentioning
confidence: 99%